2023
DOI: 10.3389/fpls.2023.1174450
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of the multi-omics reveals the stripe rust fungus resistance mechanism of the TaPAL in wheat

Abstract: Wheat is one of the major food crops in the world. However, stripe rust fungus significantly decreases wheat yield and quality. In the present study, transcriptomic and metabolite analyses were conducted in R88 (resistant line) and CY12 (susceptible cultivar) during Pst-CYR34 infection due to the limited availability of information regarding the underlying mechanisms governing wheat–pathogen interactions. The results revealed that Pst infection promoted the genes and metabolites involved in phenylpropanoid bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…(2013) , which showed the involvement of PAL in phenylpropanoid biosynthesis in both the Yr39 -mediated high-temperature adult-plant (HTAP) and Yr5 -mediated all-stage resistances of wheat. Recent report showed that TaPAL contributes to wheat resistance to Pst by regulating lignin and phenol synthesis, which was verified by the virus-induced gene silencing (VIGS) technique ( Liu et al., 2023b ).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…(2013) , which showed the involvement of PAL in phenylpropanoid biosynthesis in both the Yr39 -mediated high-temperature adult-plant (HTAP) and Yr5 -mediated all-stage resistances of wheat. Recent report showed that TaPAL contributes to wheat resistance to Pst by regulating lignin and phenol synthesis, which was verified by the virus-induced gene silencing (VIGS) technique ( Liu et al., 2023b ).…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have demonstrated that phenylalanine ammonia-lyase (PAL) functions as the gateway enzyme in phenylpropanoid metabolism and plays a key role in the response to various environmental stimuli, including pathogen infection ( Yuan et al., 2019 ; Pant et al., 2021 ; Liu et al., 2023b ). Here we show that the expression of the majority of PAL genes in wild emmer wheat is significantly increased in response to Pst infection in the two accessions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these 21 genes, such as those coding for a NBS-LRR disease resistance protein-like protein, leucine-rich repeat receptor-like protein kinase family protein, pathogenesis-related thaumatin family protein, phenylalanine ammonia-lyase, endoglucanase, MYB-related transcription factor, kinase (serine/threonine) family protein, and GDSL esterase/lipase ( [34,35,36,37,38,39,40,41], respectively), have been proven to play a role in the immune response to rust fungi. One such gene, SECCE1Rv1G0013110.1, encoding an endoglucanase (to which marker 3596652|F|0-30:A>G-30:A>G has been mapped), has previously been observed to be differentially expressed (highly up-regulated; log2 estimated fold change = 4.7) in the rye inbred line L318 infected with compatible Prs strains [41].…”
Section: Markers Located In Lo7 Genesmentioning
confidence: 99%